Raw data of physical oceanography during RV SONNE cruise SO263 - Klose, Lukas; Kleint, Charlotte; Türke, Andreas; Haase, Karsten M (PANGAEA, 2022)
Raw physical oceanography data acquired during research cruise SO263 on RV SONNE. This expedition was conducted in the North Eastern Lau Basin, Southwest Pacific. The program aimed at improving our understanding of the igneous, hydrothermal, and tectonic processes that occur during island arc and back-arc formation. Cruise SO263 operated in June 2018.
Keywords: CTD casts; CTD profiles